Economics in Context - Grant, Susan and Vidler, Chris (Auckland Heinemann, 2000)
This student book provides full coverage of economic theory for all AS and A level Economics syllabuses. It is in line with the AS/A level specifications starting September 2000. The first half of the book covers AS level Economics, whilst the second half prepares students for their A level exams.
Include Illustrations and Index.
Keywords: Auditing